2020
DOI: 10.3892/ijo.2020.5115
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase from triple‑negative breast cancer and platelets acts as an enhancer of metastasis

Abstract: Triple-negative breast cancer (TNBC), which is characterized by inherently aggressive behavior and lack of recognized molecular targets for therapy, poses a serious threat to women's health worldwide. However, targeted treatments have yet to be made available. A crosstalk between tumor cells and platelets (PLT) contributing to growth, angiogenesis and metastasis has been reported in numerous cancers. Heparanase (Hpa), the only mammalian endoglycosidase that cleaves heparan sulfate, has been demonstrated to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 75 publications
1
15
0
Order By: Relevance
“…46 Numerous studies have revealed an upregulation of HPSE expression in cells growing in hypoxic conditions and some have linked that upregulation to an increase in cell invasion. [47][48][49] There is also evidence linking hypoxia, HPSE, and upregulation of VEGF and increased angiogenesis. This is consistent with our finding that hypoxic EVs from myeloma cells promote the formation of endothelial tubes (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…46 Numerous studies have revealed an upregulation of HPSE expression in cells growing in hypoxic conditions and some have linked that upregulation to an increase in cell invasion. [47][48][49] There is also evidence linking hypoxia, HPSE, and upregulation of VEGF and increased angiogenesis. This is consistent with our finding that hypoxic EVs from myeloma cells promote the formation of endothelial tubes (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous bioinformatics and experimental studies demonstrated that HPSE promotes malignant progression, angiogenesis and metastasis in breast cancer by enhancing the crosstalk between tumor cells and platelet [ 65 ]. In this study, multi-database integration analysis indicated that high HPSE expression contributes to macrophage M2 polarization and T cell exhaustion, thus promoting tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Human MDA-MB-231-HPSE and MDA-MB-231-mock cells, which represented breast cancer cell lines with high and low expression of HPSE, were handseled by Dr. Israel Vlodavsky, the GFP inserts were performed in Glyconovo Technologies Co., Ltd, and the HPSE expression have been detected between MDA-MB-231-HPSE and MDA-MB-231-mock cells by Western blot analysis, and the specific operation method were described previously [ 65 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Yang et al is in line with our findings that the expression of heparanase was significantly higher in the metastatic group with respect to their non-metastatic counterparts and a high expression of heparanase was also significantly linked with poor disease-free survival (DFS) and overall survival (OS) in triple-negative subjects. The authors have claimed that heparanase enhanced the blood and oxygen delivery of both the breast tumours and lung metastases through a new vessel network and vascular mimicry, thus leading to tumour growth and malignant progression [ 31 ].…”
Section: Discussionmentioning
confidence: 99%